IDENTIFIKASI BEBAN KERJA DAN KELUHAN MUSKULOSKELETAL PEKERJA UNTUK MEMPERBAIKI RESPON FISIOLOGIS PADA AKTIVITAS MEMILIN SERAT AGEL DI IKM KULONPROGO: - - Kurnianingtyas, Chandra Dewi Kurnianingtyas (Jurnal Rekavasi, 2021)
The work of twisting the agel fiber at the Small Scale Industry in Kulonprogo Regency is a job that causes musculoskeletal complaints. Twisting work is done sitting on the floor on a mat, with a bent work posture and bent legs. Twisting work is monotonous and repetitive work. Twisting work gives physiological complaints in several parts of the body, namely in the upper extremity muscles and lower extremity muscles. In the upper extremity muscle, musculoskeletal complaints occur in the lower neck and right shoulder. In the lower extremity muscle, it occurs in the back, waist, and on the right thigh. Physiological complaints are influenced by the workload received by workers. Retrieval of workload method, using palpation method. Collecting data on musculoskeletal complaints using the Nordic Body Map questionnaire. The sample data of the subjects studied were 15 workers. The average workload on twisting activities is 100.2+2.31 bpm. The workload category is heavy. The average score of musculoskeletal complaints after work is 40.67+0.52. Musculoskeletal complaints experienced by workers should be reduced.